Evidence for Lgr6 as a Novel Marker of Osteoblastic Progenitors in Mice. (27th August 2018) - Khedgikar, Vikram; Lehoczky, Jessica A
ABSTRACT: Bone marrow–derived mesenchymal stem cells are an important source of osteoblasts critical for both bone homeostasis and repair. The ability to isolate, or specifically target, mesenchymal stem cells committed to the osteogenic lineage is necessary for orthopedic translational therapy efforts; however the precise molecular signature of these cells remains elusive. Previously, we identified a population of osteoprogenitor cells expressing the Wnt signaling agonist Lgr6, which contributes to the development and regeneration of the mouse digit tip bone. In our present study we build upon this data and investigate the expression of Lgr6 more broadly in the skeleton. We find that Lgr6, and closely related Lgr4, are expressed in mouse primary calvarial cells, bone marrow cells, and bone marrow–derived mesenchymal stem cells. In addition, our data demonstrates that Lgr4 expression is modestly increased throughout the differentiation and mineralization of mesenchymal stem cells. In contrast, we find Lgr6 expression to be strikingly increased upon osteogenic induction and subsequently decreased upon differentiation and mineralization. These findings provide evidence for Lgr6 as a novel marker of osteoprogenitor cells in bone marrow, which could prove useful for isolation of this population toward future research and clinical applications. © 2018 American Society for Bone and Mineral Research